A seção de ciências do Estadão: Imprensa como um patrimônio histórico-educativo - Rodrigues, Pedro Eurico (Faculdade de Educação/Universidade Estadual de Campinas, 2020)
The Document presented is an article that was taken from the newspaper O Estado de São Paulo (known as Estadão), an example of a document that unites the press, education and historical-educational heritage. As an objective, we tried to stick to the Press as a reference object, as a nucleus of information and education, since it shows ways of producing and disseminating discourses that, when preserved, expand the historical heritage and create possibilities for, through them, to recognize its importance for education. The press is understood as a historical agent that intervenes in the processes and episodes not as a simple record of events, but as an active subject in the process, interacting in the complexity of various contexts. It is worth mentioning that the press has a great pedagogical performance, in its formulating principles, because it is the one that conveys interests, disseminates aspirations, teaches by reading and, thus, is relevant to all educational dynamics.